Give Me What I Want: Identifying the Support Needs of College Student Entrepreneurs - Wang, Peng; Huang, Yangjie (Frontiers in Psychology, 2020)
To promote the maturity of college students' entrepreneurship service, we identify the main support needs of undergraduate entrepreneurs and evaluate the importance of different support needs based on the face-to-face interview data of one hundred and thirty-eight college student entrepreneurs. Further, we explore the distribution laws of the support needs in different entrepreneurial stages. We find that college student entrepreneurs have twenty different types of support needs, which can be divided into core support needs (six types), sub-core support needs (six types) and margin support needs (eight types) according to their importance. Through the cross-stage analysis of the support needs, we find that the support needs of different entrepreneurial stages are different. However, the entrepreneurial preparation stage and the start-up stage are similar strongly. The entrepreneurial failure stage is quite different from the other three stages, showing obvious heterogeneity. This study expands the research field of entrepreneurial support needs, and have positive significance for the governance of college students' entrepreneurship practice.